Understanding consumer’s behaviour through past experience, situation and subjective culture. - Su, Jie Hui. (2011)
This study argues that people’s perception of their culture, personal values, past user experiences and situations of consumption will have an impact on their preference of prestigious brand of goods. Additionally, this study proposed that people’s perception of their culture would have a moderation effect on the influence of personal values. Firstly, past user experience was found to have a robust effect for the preference of prestigious brand regardless of consumption situation. Secondly, under the condition of public consumption, there was a clear preference for prestigious good. Thirdly, people’s perception of culture was found to interact with personal value. More specifically, when perceived cultural materialism was low, personal endorsement of materialism will have no effect on the brand preference.